Drinking Water Fluoride Levels for a City in Northern Mexico (Durango) Determined Using a Direct Electrochemical Method and Their Potential Effects on Oral Health - Nelly Molina Frechero; Leonor Sánchez Pérez; Enrique Castañeda Castaneira; Anastasio Oropeza Oropeza; Enrique Gaona; José Salas Pacheco; Ronell Bologna Molina (The Scientific World Journal)
Fluoride is ingested primarily through consuming drinking water. When drinking water contains fluoride concentrations >0.7 parts per million (ppm), consuming such water can be toxic to the human body; this toxicity is called “fluorosis.” Therefore, it is critical to determine the fluoride concentrations in drinking water. The objective of this study was to determine the fluoride concentration in the drinking water of the city of Durango. The wells that supply the drinking water distribution system for the city of Durango were studied. One hundred eighty-nine (189) water samples were analyzed, and the fluoride concentration in each sample was quantified as established by the law NMX-AA-077-SCFI-2001. The fluoride concentrations in such samples varied between 2.22 and 7.23 ppm with a 4.313 ± 1.318 ppm mean concentration. The highest values were observed in the northern area of the city, with a 5.001 ± 2.669 ppm mean value. The samples produced values that exceeded the national standard for fluoride in drinking water. Chronic exposure to fluoride at such concentrations produces harmful health effects, the first sign of which is dental fluorosis. Therefore, it is essential that the government authorities implement water defluoridation programs and take preventative measures to reduce the ingestion of this toxic halogen.